Arsenic in Gold Mine Tailing and Agricultural Soil in Buru Island of Maluku - Reginawanti Hindersah; Agustinus Marthin Kalay; Robby Risamasu; Triani Dewi (Fakultas Pertanian Universitas Padjadjaran, 2020)
Contamination of heavy metal including Arsenic (As) due to mining activities decreased ecosystem quality. The objective of this study was to determine the arsenic level of tailing and agricultural soil, and evaluate the spatial distribution of As in closed gold mine and nearby agricultural area in Buru Sub-district of Maluku. Tailing and soil samples were taken by purposive method based on mining and agricultural activities. Arsenic level in tailing and soil samples was determined by Atomic Adsorption Spectrophotometer after mixed acid extraction. The study showed that gold mine increased As level in the top soil and tailing but soil of nearby agricultural area was not contaminated by As. Increased concentration of As in tailings has been verified. pH level of the agricultural area was neutral hence lowered As availability for plant.